Endogenous social norms – implications for optimal welfare state programs - Margareta Dackehag (Lund University, School of Economics and Management, Department of Economics, 2009)
This paper investigates the implications of an endogenous social work norm for the optimal welfare state program. Assuming that individual productivity is observable, the analysis finds that restrictions on program participation, implying a larger benefit to a smaller group of recipients, may be welfare improving. However, the effect of the norm is indeterminate. The disutility of non-compliance suggests a higher benefit; the endogeneity of the norm suggests a lower benefit. Assuming that individual productivity is not observable, the analysis finds that the social norm unambiguously contributes to increased program generosity. However, for sufficiently generous policies, the norm contributes to program retrenchment.
Keywords: H11; H23; H53; I38; 330; Welfare state; Social norm; Welfare analysis